Nghiên cứu khả năng quang xúc tác của BiNbO4 phân hủy metyl da cam dưới ánh sáng trong vùng khả kiến - Hà Chi, Nguyễn Thị; Dũng, Đoàn Trung; Lịm, Dương Thị; Nhiệm, Đào Ngọc (Vietnam Journal of Chemistry, 2016)
BiNbO4 nanopowders prepared by combustion urea gel method were tested photocatalytic degradation under visible – light irradiation for methyl orange solution. BiNbO4 were synthesized in optimal conditions, such as molar ratio Bi/Nb/urea = 1/1/6, pH 1, gel is formed after calcination on temperature of 120°C for 4 hours and calcination temperature from 550 oC to 1050 °C for 2 hours. The prepared samples were characterized by X-Ray diffraction, field emission scanning electron microscopy, thermal gravimetric and differential thermal analysis and ultraviolet-visible light spectrophotometry. The effect of calcination temperature on phase formation and methylene orange degradation were investigated. The result shows that the synthesized BiNbO4 for the optimized sample have size that smaller than 70 nm. Also decomposing methyl orange solution illumination for 2 hours at a rate of 0.25 g/l BiNbO4 turns liquid were capacity ≈ 99 %. After the 3rd time of regeneration the BiNbO4 also able to be used by evidence of 97.20 % of removing methyl orange.